IoT-based Flood Monitoring and Alerting System using Arduino Uno - Sukanth Behera, Saradiya Kishore Parida, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The loss of properties and living population is getting enhanced by every year due to the dynamic alterations in weather conditions which results in heavy floods. Therefore, implementation of an intelligent analysis of flood risk is necessitated for the field of research in Disaster management. This article implements an intelligent IoT-based flood monitoring and alerting system using Arduino Unomodel, where water sensors and rain sensors are utilized to alert the authorities regarding the heaviness of rain and monitoring of water level in a lake or river. This system alerts the people in nearby villages since it utilizes IoT system for notifying the village people.